2011
DOI: 10.5539/elt.v4n1p42
|View full text |Cite
|
Sign up to set email alerts
|

A Contrastive Study on Metadiscourse Elements Used in Humanities vs. Non Humanities across Persian and English

Abstract: The present study studied contrastively the use of metadiscourse in two disciplines (applied linguistics vs. computer engineering) across two languages (Persian and English). The selected corpus was analyzed through the model suggested by Hyland and Tse (2004). The results revealed the metadiscursive resources are used differently both within and between the two languages. As for the two courses, applied linguistics representing humanities relied heavily on interactive elements rather than interactional ones, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 20 publications
4
25
0
2
Order By: Relevance
“…The general trend to avoid personal pronouns in Persian academic discourse has also been confirmed in subsequent studies of personal pronouns as part of metadiscoursal devices by Zarei andMansoori (2011), Fatemi andMirshojaee (2012) and Taki and Jafarpour (2012). Taki and Jafarpour (2012) notice that Persian writers tend not to use self-mentions and when they do, they more readily employ the word 'the researcher' to refer to themselves, while Fatemi and Mirshojaee's advice for Iranian writers is to "move away from positivist impersonalized text performance towards more socialist presentation of knowledge claims and writers' stance and voice" (Fatemi and Mirshojaee 2012: 261).…”
Section: Self-reference In Research Articles Across Europe and Asiamentioning
confidence: 55%
“…The general trend to avoid personal pronouns in Persian academic discourse has also been confirmed in subsequent studies of personal pronouns as part of metadiscoursal devices by Zarei andMansoori (2011), Fatemi andMirshojaee (2012) and Taki and Jafarpour (2012). Taki and Jafarpour (2012) notice that Persian writers tend not to use self-mentions and when they do, they more readily employ the word 'the researcher' to refer to themselves, while Fatemi and Mirshojaee's advice for Iranian writers is to "move away from positivist impersonalized text performance towards more socialist presentation of knowledge claims and writers' stance and voice" (Fatemi and Mirshojaee 2012: 261).…”
Section: Self-reference In Research Articles Across Europe and Asiamentioning
confidence: 55%
“…This paper employs Hyland (2005) model as an established framework for the analysis of metatextual and interpersonal items of metadiscourse in academic writing (e.g., Bruce, 2009;Hyland, 2010;Zarei & Mansoori, 2011). One of the innovations of Hyland's model seems to be that it classifies citation as a part of metadiscourse (cf.…”
Section: Discussionmentioning
confidence: 98%
“…In another study, Zarei and Mansoori (2011) investigated the use of metadiscourse in two disciplines (applied linguistics vs. computer engineering) within two languages (Persian and English). Analysis of data showed that the metadiscursive resources used differently both within and between the two languages.…”
Section: Metadiscourse Investigationsmentioning
confidence: 99%